Challenges and Debates of Agritourism Development A Case Study of Shahrud Rural Area - محمد رضا رضوانی; Mohammad Najjarzadeh; ذبیح الله ترابی (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2017)
Agritourism has become increasingly important in recent years and differentcountries have put a lot of efforts to promote it. Experts believe that agritourismcan play an important and constructive role in sustainable agricultural andrural development as a new strategy. Accordingly, the present study analyzes thechallenges and issues facing agritourism development in the rural areas ofShahrud city using a qualitative research design and purposive sampling. Datawere collected via holding interviews and meetings with three groups ofstakeholders (farmers, tourists and managers) based on the modified NominalGroup Technique (NGT) in the summer of 2015. The central question raised atthe meeting was: What are the challenges and issues of agritourism developmentin the rural areas of Shahrud city? According to the results, the stakeholderscategorized the challenges and issues facing agritourism development inShahrud into six groups: distance from major population resources,comprehensive national and regional policies, awareness and training,marketing, customs, and laws